Sugammadex: Breaking Through Residual Paralysis after Neostigmine’s Limits - Aparna Bagle; Sania Rodrigues (Journal of Clinical and Diagnostic Research)
Persistent neuromuscular blockade following the use of Neuromuscular Blocking Agents (NMBAs) remains a significant postoperative concern, often resulting in delayed recovery and prolonged stays in the Post- Anaesthesia Care Unit (PACU). It occurs when the effects of NMBAs are not fully reversed before emergence from anaesthesia, leading to complications such as hypoxaemia, impaired airway reflexes, aspiration, and respiratory failure. Despite the use of traditional anticholinesterase reversal agents, incomplete recovery of neuromuscular function can still occur due to factors such as improper dosing of reversal agents, variability in patient response to NMBAs, and the lack of adequate neuromuscular monitoring during surgery. These challenges pose risks for patients and highlight the need for effective management strategies. This report describes two cases of residual neuromuscular blockade that persisted despite the administration of anticholinesterase agents. Both patients experienced delayed recovery of muscle strength in the immediate postoperative period, raising concerns about inadequate blockade reversal. In both cases, the administration of sugammadex, a novel selective relaxant-binding agent, led to rapid and complete resolution of the neuromuscular blockade. These cases emphasise the efficacy of sugammadex in addressing persistent neuromuscular blockade, particularly in situations where traditional reversal agents fail to achieve full recovery.